Perceived social support as a predictor of academic success in Spanish university students - Tinajero, Carolina; Martínez-López, Zeltia; Rodríguez, M. Soledad; Páramo, M. Fernanda (Anales de Psicología / Annals of Psychology, 2020)
Perceived social support is considered a key factor for reducing the risk of psychological distress, academic failure and student withdrawal from university; however, research concerning how social support may influence academic performance in undergraduate students is scarce. This study aimed to examine the relation of different provisions and sources of perceived social support with academic achievement of Spanish university students in their first and third year. The sample consisted of 219 emerging adults, 149 women and 70 men, of average age 18.01 years (SD= 0.46), enrolled on different degree courses at a public Spanish university. Data were collected during the first academic year (time 1) and again during the third academic year (time 2). Regression analysis of the data showed that different dimensions of social support predicted academic success throughout a period of two years. The study findings could be used to help university counsellors and administrators refine programmes and policies aimed at enhancing students’ adjustment and academic achievement.